2022
DOI: 10.3748/wjg.v28.i3.381
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative mortality and morbidity after D2 lymphadenectomy for gastric cancer: A retrospective cohort study

Abstract: BACKGROUND Surgery for gastric cancer is a complex procedure and lymphadenectomy is often mandatory. Postoperative mortality and morbidity after curative gastric cancer surgery is not insignificant. AIM To evaluate the factors determining mortality and morbidity in a population of patients undergoing R0 resection and D2 lymphadenectomy for gastric cancer. METHODS A retrospective analysis of clinical data and pathological characteristics (age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
0
17
0
1
Order By: Relevance
“…LNM strongly affects the prognosis[ 14 , 54 ]. This is a topic of not negligible importance because EGC is believed to be a curable albeit malignant disease.…”
Section: Treatmentmentioning
confidence: 99%
“…LNM strongly affects the prognosis[ 14 , 54 ]. This is a topic of not negligible importance because EGC is believed to be a curable albeit malignant disease.…”
Section: Treatmentmentioning
confidence: 99%
“…Hayashi et al [ 12 ] recommended the retrieval of more than 40 LNs after total gastrectomy for stage III patients, whereas Lu et al [ 13 ] suggested that harvesting 21 LNs might represent a superior cut-off point for radical gastrectomy to better determine the prognosis of the patients. Total LN number is a powerful qualifier of staging and survival information for GC [ 31 ] without increased postoperative mortality [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of lymph node (LN) metastasis is one of the most significant prognostic factors in patients with gastric cancer (GC) [ 1 , 2 , 3 ]. Metastases occur during the early stages of the disease [ 3 , 4 , 5 , 6 ], and because their pre- and intra-operative diagnosis remain unreliable, a D2 lymphadenectomy should be performed whenever nodal involvement is suspected [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which is the most appropriate lymphadenectomy to perform, to offer the best oncological outcome without increasing postoperative morbidity and mortality, is in fact controversial, due to the differences in results between East and West and between high and low volume centres[ 11 ]. This aspect is not of negligible importance, since LN metastasis, which can also appear in the early stages of the disease, is one of the most significant prognostic factors in these patients[ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%